(untitled) (Práxis Educativa, 2022)
This article presents a part of an investigation that assessed the processes of institutionalization of education on ethnic-racial relations in the Pedagogy courses at the Federal University of Rio Grande do Sul, the Federal University of Santa Catarina and the Federal University of Paraná, Brazil. For the study, it was opted for the content analysis of the Pedagogical Projects, Programs and Teaching Plans of the subjects and interviews with course professors, seeking to know the experiences of implementing Law no. 10.639/2003 and National Curriculum Guidelines for the Education of Ethnic-Racial Relations and for the Teaching of Afro-Brazilian and African History and Culture. Theoretical and methodological lenses subsidized by epistemologies that stress the academic canon marked by colonialism, Eurocentrism and whiteness are presented, in order to produce a positioned, partial and localized knowledge. The study found the insurgency of a black intellectuality proposing epistemological changes in Pedagogy courses, especially through the proposition of mandatory curricular components from a racial perspective. Keywords: Black intellectuality. Education of ethnic-racial relations. Pedagogy courses.